2018
DOI: 10.1097/aog.0000000000002374
|View full text |Cite|
|
Sign up to set email alerts
|

Foley Plus Oxytocin Compared With Oxytocin for Induction After Membrane Rupture

Abstract: ClinicalTrials.gov, NCT01973036.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 18 publications
2
23
0
1
Order By: Relevance
“…A recent randomized controlled trial comparing the Foley catheter with concurrent oxytocin versus oxytocin alone in women with PROM reported that cervical ripening with the Foley catheter in addition to oxytocin did not shorten the time to delivery but significantly increased rates of chorioamnionitis compared with oxytocin alone (8 vs. 0%) . 45 The number of vaginal examinations was similar between groups. The rate of fetal scalp electrode use was higher in the Foley catheter group versus the oxytocin group; however, this was not related to the higher rates of chorioamnionitis with the Foley catheter.…”
Section: Clinical Vignettes To Help Guide Treatment Selectionmentioning
confidence: 73%
See 1 more Smart Citation
“…A recent randomized controlled trial comparing the Foley catheter with concurrent oxytocin versus oxytocin alone in women with PROM reported that cervical ripening with the Foley catheter in addition to oxytocin did not shorten the time to delivery but significantly increased rates of chorioamnionitis compared with oxytocin alone (8 vs. 0%) . 45 The number of vaginal examinations was similar between groups. The rate of fetal scalp electrode use was higher in the Foley catheter group versus the oxytocin group; however, this was not related to the higher rates of chorioamnionitis with the Foley catheter.…”
Section: Clinical Vignettes To Help Guide Treatment Selectionmentioning
confidence: 73%
“…The rate of fetal scalp electrode use was higher in the Foley catheter group versus the oxytocin group; however, this was not related to the higher rates of chorioamnionitis with the Foley catheter. Due to the increased risk of infection with prostaglandins and mechanical methods, 43 44 45 the use of oxytocin without cervical ripening is recommended for this patient .…”
Section: Clinical Vignettes To Help Guide Treatment Selectionmentioning
confidence: 99%
“…Different methods of OT infusion may result in discrepancies in labor induction. In patients with prelabor rupture of membranes, a Foley catheter with OT does not shorten the time to delivery compared with OT alone but may contribute to the increase in the chance of intraamniotic infection [56]. Pulsatile administration can prominently reduce the dose of OT required to induce labor [55].…”
Section: Labor Inductionmentioning
confidence: 99%
“…Die Nutzung von Ballonkathetern oder Dilatatoren kann aktuell nicht uneingeschrĂ€nkt empfohlen werden. Die Studienlage bezĂŒglich einer erhöhten Infektionsrate ist heterogen, wobei manche Autoren einen Zusammenhang zeigen konnten [28], andere jedoch nicht [29] [4,37]. Eine wiederholte Gabe ist mit einem geringeren Geburtsgewicht und kleinerem Kopfumfang assoziiert [4].…”
Section: Merkeunclassified